ADB First Decade 1966-1976 updated edition. (Metro Manila, Philippines Asian Development Bank, 2017)
This first volume from the series ADB through the Decades explains how the idea of a regional development bank for Asia emerged and gained support, and how ADB established itself as a sound and credible institution.
Keywords: Public administration -- Developing countries..; Electronic books